Teaching the principles of universal design - Baizhanova Жазира; Sarinzhapova Меруерт (Рroblems of engineering and professional education, 2022)
The article presents the basic principles of organizing an inclusive interior to create an accessible environment not only for people with disabilities and the elderly, but also for all categories of the population. The aspects of designing an accessible environment for people with disabilities are studied, as well as the circumstances that determine and justify the use of special equipment.